Crude Oil Price Fluctuation and Economic Growth: ARDL Model Approach - Doan Van Dinh (International Journal of Energy Economics and Policy, 2022)
The relationship between crude oil prices and countries' GDP is used to consider whether crude oil prices impact their economic growth and the extent to which they are impacted. To explore and investigate this relationship, the autoregressive distributed lag model (ARDL) was combined with the unit root, Pearson's correlation (two-tailed) tests, and time series collected from 1991 to 2020 to explore their relationship. The crude oil prices affecting Vietnam, China, and South Korea are -52.6%, -37.6%, -48.5%, respectively, while other countries have a minimal impact, such as Thailand (-20.3 %), Singapore (-24.7%), Indonesia (11.1%), Malaysia (-23.4%), Japanese (-18.3%) and America (-12.8%). Crude oil prices negatively impact all countries except Indonesia. In addition, the empirical results provide accurate forecasting and alternative energy policymaking for micromanagers who set sustainable economic growth goals and have short-term and long-term economic development strategies.